Proceedings of the 50th Hawaii International Conference on System Sciences (2017) 2017
DOI: 10.24251/hicss.2017.721
|View full text |Cite
|
Sign up to set email alerts
|

How Espoused Culture Influences Misuse Intention: A Micro-Institutional Theory Perspective

Abstract: Following Willson and Warkentin's [42]

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
4
0

Year Published

2017
2017
2024
2024

Publication Types

Select...
3
1
1

Relationship

0
5

Authors

Journals

citations
Cited by 5 publications
(4 citation statements)
references
References 35 publications
0
4
0
Order By: Relevance
“…Following other IS scholars, IS misuse can take the shape of occupational fraud (eg, Cappelli et al, 2012; Dhillon, 1999; ReSpa, 2013; Willison, Lowry, & Paternoster, 2018), deliberate misuse of IS resources and criminal policy violations such as unauthorized access to information and modification (D'Arcy & Hovav, 2009; Hu, Xu, Dinev, & Ling, 2011; Straub, 1990), as well as software piracy (eg, D'Arcy & Hovav, 2007; Lowry, Zhang, & Wu, 2017; Peace, Galletta, & Thong, 2003). Besides, it can take the shape of insertion of malicious codes in extreme cases (Hutchings & Jorna, 2015; Lee, Lee, & Yoo, 2004), or purposeful leaking of confidential data for personal gains (Hovav, 2017; Hu et al, 2011; Smith & Jorna, 2011; Willison et al, 2018), theft and embezzlement (Hutchings & Jorna, 2015; Inuwa, Ononiwu, et al, 2019; Shaw & Stock, 2011) and cover‐up for mistakes in computer systems (Dhillon & Moores, 2001). Espionage (Shaw & Stock, 2011; Shropshire, 2009), sabotage (eg, creating backdoor accounts to syphon money; eg, Shropshire, 2009), and committing intentional errors (eg, Lowry, Posey, Bennett, & Roberts, 2015; Posey, Bennett, & Roberts, 2011) among others can occur to increase the list of such behaviors.…”
Section: Literature Reviewmentioning
confidence: 99%
“…Following other IS scholars, IS misuse can take the shape of occupational fraud (eg, Cappelli et al, 2012; Dhillon, 1999; ReSpa, 2013; Willison, Lowry, & Paternoster, 2018), deliberate misuse of IS resources and criminal policy violations such as unauthorized access to information and modification (D'Arcy & Hovav, 2009; Hu, Xu, Dinev, & Ling, 2011; Straub, 1990), as well as software piracy (eg, D'Arcy & Hovav, 2007; Lowry, Zhang, & Wu, 2017; Peace, Galletta, & Thong, 2003). Besides, it can take the shape of insertion of malicious codes in extreme cases (Hutchings & Jorna, 2015; Lee, Lee, & Yoo, 2004), or purposeful leaking of confidential data for personal gains (Hovav, 2017; Hu et al, 2011; Smith & Jorna, 2011; Willison et al, 2018), theft and embezzlement (Hutchings & Jorna, 2015; Inuwa, Ononiwu, et al, 2019; Shaw & Stock, 2011) and cover‐up for mistakes in computer systems (Dhillon & Moores, 2001). Espionage (Shaw & Stock, 2011; Shropshire, 2009), sabotage (eg, creating backdoor accounts to syphon money; eg, Shropshire, 2009), and committing intentional errors (eg, Lowry, Posey, Bennett, & Roberts, 2015; Posey, Bennett, & Roberts, 2011) among others can occur to increase the list of such behaviors.…”
Section: Literature Reviewmentioning
confidence: 99%
“…Normative pressure occurs when social actors voluntarily, but unconsciously, imitate the same attitudes, behaviors and practices of other actors (Shi, Shambare, & Wang, 2008). According to Hovav (2017), normative pressure is the individual's belief of their surroundings environment which is it can influence the individual's behavior on the technology adoption. This pressure comes from the professional possessed by individuals through the formal education they have had.…”
Section: Volume 4 Issuementioning
confidence: 99%
“…While prior information systems research has explored the potential impact of national culture on IT adoption and implementation for many years (Cardon and Marshall, 2008;Veiga et al, 2001), the behavioral information security literature has just started to investigate the role that national cultural differences play in security-related actions (Aurigemma and Mattson, 2018;Chen and Zahedi, 2016;Dinev et al, 2009;Dols and Silvius, 2010;Hovav, 2017;Hovav and D'Arcy, 2012;Karjalainen et al, 2013;Lowry et al, 2014). For instance, Hovav and D'Arcy (2012) explored the effect of national culture on employee information system misuse and found that there were significant differences in security intentions and behavioral antecedents between US and South Korean participants across a set of the same misuse scenarios.…”
Section: Ics 271mentioning
confidence: 99%